SEMANTIC ANALYSIS ON JAPANESE IDIOM WHICH LEXEM HAND - Fitria Ita (Universitas Diponegoro, 2014)
This research is aimed to explain relation of lexical meaning and figurative meaning on Japanese idiom which use part of body`s hand as well as to find out the change meaning of hand on Japanese idiom. The conclusion of the semantic analysis on Japanese idiom which use part of body`s hand is: (1) Japanese idiom have two syntaxes that is positive verb and negative form. (2) te + ga + Adj. structure syntaxes`s idiom doesn`t have negative form. (3) one idiom possibly have different meaning (4) idiomatic meaning can be find out when right substance with left substance have compared.